Selective Cu and Ni-MOFs as pre-catalysts for the hydrogenation of furfural to furfuryl alcohol† - Pamela S Moyo; Banele Vatsha; Gift Mehlana; Leah C. Matsinha; Banothile C. E. Makhubela (Royal Society of Chemistry, 2023)
In this work, we report the design of one-dimensional (1D) metal–organic framework containing Cu(II) and Ni(II) active sites using a N,N′-bis-(4-pyridyl)isophthalamide linker to form MOF 1 [Cu1/2(L1)(NO3−)·DMF] and MOF 2 [Ni1/2L1Cl]. The MOFs were evaluated as heterogeneous catalysts for the hydrogenation of furfural to furfuryl alcohol. MOF 2 catalyst showed impressive performance with conversion of FF (81%) and selectivity towards FA (100%). Post-experimental characterisation showed that the structural integrity of the MOF 2 was not altered after catalysis. The catalyst could also be reused several times without any significant loss in activity and selectivity. Furthermore, a possible plausible reaction mechanism of the reaction over MOF 2 was proposed.